Effect of dendritic cell vaccine on blood redox status in patients with cervical cancer - A. P. Menshenina; I. A. Goroshinskaya; E. M. Frantsiyants; T. I. Moiseenko; E. V. Verenikina; I. V. Kaplieva; L. A. Nemashkalova (Исследования и практика в медицине)
Purpose of the study. The purpose of the study was to evaluate the dynamics of parameters of malondialdehyde (MDA), reduced glutathione and antioxidant enzyme activity in patients with advanced cervical cancer (CC) receiving anticancer treatment with dendritic cell vaccine (DCV).Patients and methods. Levels of malondialdehyde (MDA), reduced glutathione and antioxidant enzyme activity were studied in 27 patients aged 27–65 years with advanced primary and recurrent CC receiving chemotherapy (CT) with DCV or DCV as monotherapy at a dose of 10 million cells intradermally once a week. The same indices were studied in 20 healthy women from the comparison group.Results. The majority of patients showed the initial increase of MDA: in blood plasma by an average of 66.7 %, in red blood cells – statistically insignificant. After CT, MDA levels were elevated respectively in primary and recurrent patients in erythrocytes by 85.6 % and 96.4 % compared to donors, and by 53.9 % and 33.7 % compared to the initial values; the levels in plasma were elevated by 79.8 % and 57.1 % compared to donors. After 5–7 DCVs in combination with CT, MDA levels in erythrocytes and in blood plasma were similar to the donor values. MDA in erythrocytes of patients receiving DCV without CT decreased by 36 % compared to initial values. Oxidase activity of ceruloplasmin, initially increased by 34.2–57.1 %, normalized after DCV. Superoxide dismutase activity decreased by 16.7–27.3 % after 4–6 DCVs and normalized after 7 DCVs. Catalase activity, initially reduced by more than 40 %, remained 20–38 % lower than the norm at all stages of DCV. In this setting, hydrogen peroxide was probably inactivated by glutathione peroxidase whose activity was increased at all stages of treatment and decreased only when MDA was normalized after 7 DCVs.Conclusion. Administration of 5–7 DCVs in combination with CT or as monotherapy to patients with advanced CC normalizes parameters of free radical oxidation and antioxidant system of the blood.